Biodiversity, Medicinal Flora, And Human Health: An EcoHealth Perspective (International Journal of Environmental Sciences, 2025)
Biodiversity forms the backbone of ecosystem services vital for human health, with medicinal flora playing a pivotal role in traditional and modern healthcare systems. This paper explores the intricate relationships between biodiversity, the conservation of medicinal plants, and their implications for human health through the lens of the eco-health approach. It highlights the importance of preserving biodiversity as a reservoir of therapeutic agents and examines the threats posed by environmental degradation, climate change, and habitat loss. The paper also addresses strategies to integrate traditional knowledge and modern science for sustainable health solutions, advocating for policies that bridge environmental conservation and public health.